Pengembangan Media Pembelajaran Video Animasi Berbasis Animaker Pada Mata Pelajaran Ekonomi Kelas X Di SMAN 1 Sreseh - Holifah, St.; Mariatun, Ika Lis (Universitas Negeri Surabaya, 2024)
This research is research into the development of animaker-based animated video learning media products in class X economics subjects at SMAN 1 Sreseh. This research aims to (1) Develop animaker-based animated videos into learning media for economics subjects at SMAN 1 Sreseh. (2) Knowing the feasibility of animaker-based animated videos as economic learning media for students at SMAN 1 Sreseh that are being developed. (3) Knowing the use of learning media using Animaker-based animated videos can improve the learning outcomes of class X students at SMAN 1 Sreseh. This development research is carried out using R&D (research and development) which consists of potential and problems, collecting information, product design, design validation, design improvement, product trials, product revisions, usage trials, product revisions, and product manufacturing. Based on this research, for the assessment of material experts, the percentage score was 84% ??in the (very feasible) category, media experts had a percentage score of 80% in the (eligible) category, field practitioners scored a percentage of 98% in the (very feasible) category, and improved learning outcomes scored 0 .85% or 85% with category (very decent). Based on the pretest posttest, student learning outcomes were initially 60-75, after using learning media using Animaker it was 90-95, resulting in an increase in student learning outcomes.